Evaluation of physicochemical variability of sustainable aviation fuels - Oldani, Anna L.; Solecki, Alexandra E.; Lee, Tonghun (Frontiers in Energy Research, 2022)
leveraging data from the FAA Alternative Jet Fuels Test Database (AJFTD). The AJFTD, containing fuel sample records of conventional and sustainable aviation fuels to date, was developed by the PIs through the FAA Center of Excellence (ASCENT). With the development of SAF from various feedstocks and processing methods, new approval processes have been developed to accommodate the changing jet fuel landscape. To control for these differences, approval procedures were designed as each new fuel category came through the development pipeline. However, recent studies have suggested that rather than feedstock or processing method, chemical properties and fuel performance can be accurately judged by considering fuel composition characteristics such as carbon chain length, hydrocarbon class, and branching level. To quantify the variability present in recently approved jet fuels, this paper evaluates physicochemical property variability and provides relevant thermophysical property relations for conventional and alternative jet fuels with a discussion of efforts to streamline approval, reducing the time and cost of bringing new SAF to future markets. The key results of this evaluation demonstrate that although significant variability exists in the thermophysical relations for SAF as compared to conventional fuels, the expected ranges for the examined properties remain within specification requirements as detailed in the American Society for Testing and Materials (ASTM) D7566 standard for aviation fuels containing synthesized hydrocarbons.